An Offline and Online Approach to the OLTC Condition Monitoring: A Review - Ismail F.B.; Mazwan M.; Al-Faiz H.; Marsadek M.; Hasini H.; Al-Bazi A.; Yang Ghazali Y.Z. (MDPI, 2023)
Damage detection; Disaster prevention; Electric utilities; Outages; Voltage control; Condition; Diagnostic methods; Electricity distribution; Energy; Incipient faults; Monitoring methods; Offline; On-load tap changer; Onload tap changer; Transformer; Condition monitoring